Principles of proportionality and reasonability in individualization foundation in criminal judgment (SCIÉNDO INGENIUM, 2021)
The present investigation was developed with the purpose of determining the relationship between the principles of proportionality and reasonableness in the individualization and foundation of punishment, the study design is correlational descriptive and the applied research methods are deductive and inductive, it has been used Two reliable questionnaires for data collection. Our problem investigated is: What is the relationship between the principles of proportionality and reasonableness in the correct individualization and justification of punishment? To this end, questionnaires were carried out on proportionality and reasonableness in the individualization and justification of the sentence. Our main conclusion to achieve a good application of the principles of proportionality and reasonableness, is to base well the penalty on crimes with clear and updated objectives.
Keywords: Proportionality; reasonableness; criminal sentence; legal principles; crimen prevention